IMPLEMENTATION OF GUIDED INQUIRY INTERACTIVE REINFORCEMENT TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ SCIENTIFIC LITERACY - Permatasari, Brigita Berlian; Erman, Erman (PT. Jurnal Center Indonesia Publisher, 2026)
The low level of students’ scientific literacy indicates the need for learning approaches that can train scientific thinking process through inquiry activities. This study aims to compare the effectiveness of Guided Inquiry Interactive Reinforcement learning with Guided Inquiry learning without Interactive Reinforcement on the topic of global warming in improving junior high school students’ scientific literacy. This research employed a quantitative approach with a quasi-experimental design conducted at a public junior high school in Sidoarjo Regency. This research subjects were students of class IX F as the experimental class and class IX B as the control class. Data were collected through scientific literacy test instrument, learning implementation observation sheets, and student response questionnaires. The test data were analyzed using the Mann-Whitney U test, effect size calculation, and N-Gain, while the data from the observation of learning implementation and student response questionnaires were analyzed descriptively using quantitative methods. The results showed that there was a significant difference in scientific literacy between the experimental class and the control class with an Asymp. Sig. (2-tailed) value of <0,001. The effect size calculation obtained a value of , categorized as a large effect, indicating a very strong influence. The improvement in scientific literacy in the experimental class was higher with an average N-Gain of 0,927 (high category) compared to the control class with 0,783 (high category). The level of scientific literacy also increased from level 2 in the pretest to level 6 in the experimental class and level 5 in the control class in the posttest. These results were supported by the implementation of learning in both classes, which was categorized as very good, and student responses that showed very good criteria with a higher percentage in the experimental class. Based on these findings, the Guided Inquiry Interactive Reinforcement learning model is proven to be more effective in improving junior high school students’ scientific literacy. This learning model is recommended to be applied to science topics that have contextual characteristics in order to enhance students’ scientific literacy.